DNA repair mechanisms: Exploring potentials of nutraceutical - S. Ahmad; M.L. Tan; Shahrul Hamid (Journal of Functional Foods, 2023)
Cardiovascular disease is among the major causes of death worldwide. It is associated with several factors, including genetics, high-fat intake, smoking, hypertension, diabetes, and general lifestyle. In the pathogenesis of cardiovascular diseases, there is a sudden onset of radical oxygen species production. This causes DNA damage, and ultimately leads to cell death. Several forms of DNA damage have been associated with cardiovascular disease. Therefore, it is crucial to reduce the reactive oxygen species (ROSs) as a preventive measure. The diversity of the plant kingdom provides valuable nutrients to conserve DNA functionality. This review aims to present the fundamental principles of various types of DNA repair mechanisms and describes the involvement of nutraceuticals and their bioactive compounds in mitigating DNA damage.